"Financial Crimes Originate from Financial Illiteracy" The Mauritian Context - Fulena, Viraj; Chittoo, Hemant B. (Journal of Business, Management, and Social Studies, 2023)
This study aims to explore the connection between financial illiteracy and financial crimes. Quantitative data analysis was conducted to determine whether there is a relationship between the two variables. A questionnaire was selected for data collection, the questionnaire is divided into 21 questions and segmented into different parts. The study found that 41.2% of the audience were able to distinguish between money and finance, 88.2% of the audience were banked, 45.1% felt comfortable and confident in their financial knowledge, 41.2% of the audience acknowledged the role of financial institutions in combating financial crimes and promoting financial literacy, and 60% of the audience identified a connection between financial literacy and financial crimes. The results obtained from quantitative data analysis indicate the need for further study, as certain aspects of financial literacy and their relationship with financial crimes require more attention. The study results will contribute to the understanding of the importance of financial education and its impact on reducing financial crimes.